The Influence of Intellectual Capital, Market Value, and Earnings Per Share on Stock Returns - Sulistiani, Astri; Ryanto, Fuad Ramdhan (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2024)
This research aims to determine the influence of Intellectual Capital, Market Value, and Earnings per share on stock returns in financial sector companies for the 2020-2022 period. The population used in this research is financial sector companies on the Indonesia Stock Exchange (BEI) for the 2020-2022 period. number of samples 94 samples. This type of research is quantitative. Secondary data is used in data collection and sampling using purposive sampling techniques with multiple linear data analysis. Using SPSS 23. The results of the research are that the Intellectual Capital and Market Value variables partially have no effect on stock returns. while Earning Per Share has a positive effect on stock returns. In simultaneous testing, the intellectual capital, market value and earnings per share variables together have no effect on stock returns.